(untitled) (Neo Science Peer Reviewed Journal, 2024)
In this article, the questions of stylistic transformations in literary translation are considered. Attention is paid to the ratio of the number of stylistic transformations in translations and their relationship with the adequacy of the translation into Russian. The article presents the results of a comparative analysis of one of the most famous Muriel Spark’s stories “Portobello Road” and two translations of this work. Particular attention is paid to the question of achieving communicative and pragmatic effect of translated texts, a necessary condition of which is the use of stylistic transformations. The novelty of the study is in identification of the most common stylistic transformations in translations used to achieve their adequacy and the original communicative and pragmatic effect of the text by preserving the author’s intention and original style. The relevance of the study is due to the lack of developed methods for determining the communicative and pragmatic effect of translated texts, as well as the task of improving the quality of translations and the need to determine the typical stylistic transformations that determine the pragmatic and aesthetic compliance of translated texts. The classifications of stylistic transformations developed in the theory of translation are given, their comparative analysis is carried out. It is proved that the emotional and expressive vocabulary and the adjectives are stylistically transformed most often, transformations being: replacement (remetaphorization and metonymical transformations) and additions (metaphorization and phraseologization). It is emphasized that they serve to achieve the pragmatic effect of the artwork.